Spatial Mapping and Profiling of Metabolite Distributions during Germination . Issue 4 (20th June 2017) - Feenstra, Adam D.; Alexander, Liza E.; Song, Zhihong; Korte, Andrew R.; Yandeau-Nelson, Marna D.; Nikolau, Basil J.; Lee, Young Jin
Abstract : A combination of metabolomics and mass spectrometry imaging provides new insights in metabolic processes during the germination of maize seeds. Abstract: Germination is a highly complex process by which seeds begin to develop and establish themselves as viable organisms. In this study, we utilize a combination of gas chromatography-mass spectrometry, liquid chromatography-fluorescence, and mass spectrometry imaging approaches to profile and visualize the metabolic distributions of germinating seeds from two different inbreds of maize ( Zea mays ) seeds, B73 and Mo17. Gas chromatography and liquid chromatography analyses demonstrate that the two inbreds are highly differentiated in their metabolite profiles throughout the course of germination, especially with regard to amino acids, sugar alcohols, and small organic acids. Crude dissection of the seed followed by gas chromatography-mass spectrometry analysis of polar metabolites also revealed that many compounds were highly sequestered among the various seed tissue types. To further localize compounds, matrix-assisted laser desorption/ionization mass spectrometry imaging was utilized to visualize compounds in fine detail in their native environments over the course of germination. Most notably, the fatty acyl chain-dependent differential localization of phospholipids and triacylglycerols was observed within the embryo and radicle, showing correlation with the heterogeneous distribution of fatty acids. Other interesting observations include unusual localization of ceramides on the endosperm/scutellum boundary and subcellular localization of ferulate in the aleurone.